The Effects of Wenxin Keli on Left Ventricular Ejection Fraction and Brain Natriuretic Peptide in Patients with Heart Failure: A Meta-Analysis of Randomized Controlled Trials. (27th April 2014) - Chen, Yu; Xiong, Xingjiang; Wang, Chunmei; Wang, Chenggang; Zhang, Ying; Zhang, Xingyong; Gao, Yonghong; Xing, Yanhui; Li, Jun; Wang, Jie; Liu, Xiaoqiu; Xing, Yanwei
Abstract : Objective . To evaluate the beneficial and adverse effects of Wenxin Keli (WXKL), either alone or in combination with Western medicine, on the left ventricular ejection fraction (LVEF) and plasma brain natriuretic peptide (BNP) in the treatment of heart failure (HF). Methods . Seven major electronic databases were searched to retrieve potential randomized controlled trials (RCTs) designed to evaluate the clinical effectiveness of WXKL, either alone or in combination with Western medicine, for HF, with the LVEF or BNP after eight weeks of treatment as main outcome measures. The methodological quality of the included studies was assessed using criteria from the Cochrane Handbook for Systematic Review of Interventions, Version 5.1.0, and analyzed using RevMan 5.1.0 software. Results . Eleven RCTs of WXKL were included. The methodological quality of the trials was generally evaluated as low. The risk of bias was high. The results of the meta-analysis showed that WXKL, either alone or in combination with Western medicine, was more effective in LVEF and BNP, compared with no medicine or Western medicine alone, in patients with HF or HF complicated by other diseases. Five of the trials reported adverse events, while the others did not mention them, indicating that the safety of WXKL remains uncertain. Conclusions . WXKL, either alone or in combination with Western medicine, appears to be more effective in improving the LVEF and BNP in patients with HF and HF complications.